SHONA LITURGICAL SERIES: 29 small LP records. Mambo Press, P.O. Box 779, Gwelo, Rhodesia, 70c each - Basil, Brother (International Library of African Music, 1971)
pages: 100
Keywords: Shona (African people); African Music